Modelling of lead removal by aquatic an moss - Martins, Ramiro (2011)
Aquatic bryophytes are frequently used as biomonitors for trace metals in aquatic ecosystems. Nevertheless, their special characteristics also allow using them as biosorbents to clean industrial wastewaters. As biosorption is a low cost and effective method for treating metal-bearing wastewaters, understanding the process kinetics is relevant for design purposes. In this study, the ability of the aquatic bryophyte Fontinalis antipyretica to remove lead from simulated wastewaters was evaluated. Three kinetic models (pseudo-first order, pseudo-second order and Elovich) were fitted to the experimental data and compared by the F-test. Previously, the effect on biosorption of parameters such as the initial solution pH, contact time and initial metal ion concentration was investigated. The initial pH of the solution was found to have an optimum value is in the range 4.0-6.0. The equilibrium sorption capacity of lead by Fontinalis antipyretica increased with the initial metal concentration. For an initial metal concentration of 10 mg L-1, the uptake capacity at equilibrium was 4.8 mg g-1. Nevertheless, when the initial concentration increased up to 100 mg L-1, the uptake of lead was 10 times higher. The pseudo-second order biosorption kinetic model provided the better correlation with the experimental data (R2=1.00). The applicability of the Langmuir and Freundlich adsorption isotherms to the present system was also assessed. The maximum lead sorption capacity by Fontinalis antipyretica was 68 mg g-1.